Detection of the surface-exposed 18-kilodalton binding protein in Chlamydia trachomatis by immunogold staining. - Gray, G J (1990)
Dot-blot analysis of Chlamydia trachomatis elementary bodies (EBs) with monospecific polyclonal antibodies demonstrated that the 18-kilodalton binding protein is surface exposed. Immunoelectron microscopy with whole serovar L2 EBs and ultrathin sections confirmed this finding. In addition, only the extracellular EBs and not the intracellular reticulate bodies were labeled with immunogold.